The Effect of Career Interest on Hospitality Career Choice among Diploma IV Hotel Management Students at Universitas Negeri Padang - Fauziah Fauziah; Kurnia Illahi Manvi (Journal of Multidimensional Management, 2026)
This study investigates how career interest shapes hospitality career choice among students in the 2022 cohort of the Diploma IV Hotel Management Program at Universitas Negeri Padang. A quantitative causal-associative design was applied, involving 100 respondents selected through simple random sampling from a population of 133 students. Data were collected using a five-point Likert-scale questionnaire and analyzed through simple linear regression with SPSS 27. The results show that students reported a strong level of career interest, with a mean score of 4.26 and a respondent achievement rate (TCR) of 85.19%, while hospitality career choice was also rated highly, with a mean score of 4.27 and a TCR of 85.44%. Regression analysis indicated that career interest had a positive and significant influence on hospitality career choice, as reflected in the equation Y = 5.373 + 1.119X, with t = 33.382 and p < 0.001. Career interest explained 91.9% of the variance in career choice (R² = 0.919), although this strong explanatory value should be interpreted carefully because both constructs are closely related and the respondents came from a relatively homogeneous vocational education background. The findings support the relevance of Social Cognitive Career Theory in explaining students’ career direction in hospitality education and suggest that career interest needs to be strengthened through practice-based learning, internship experience, industry exposure, and structured career guidance so that students can translate their interest into realistic and informed career choices in the hospitality sector.